‘Who Does He Think He Is?’:An Interpretation of Christ's Self-Witness - Hutchison, Harry (Scottish journal of theology, 1961)
No more important question can be asked than the wellknown New Testament inquiry, ‘What think ye of Christ?’—unless it be the question, ‘What thinks Christ of Himself?’ In past decades this question has not, perhaps, been asked as often as it might. Is there a reason for this? Undoubtedly there is. This (it will be claimed) is so controversial a question, with reputable scholars taking widely divergent views, that there seems little point in giving it the importance which many of our forefathers gave to it.